Factors influencing the citation behavior of Pakistani novice LIS researchers. (June 2023) - Warraich, Nosheen Fatima; Ali, Irfan; Tahira, Muzammil; Raza, Shahzada Nadeem
This study aims to understand the citation behavior of LIS research graduates in terms of their citation practices, citation motivation with the perceived quality and trustworthiness of cited sources. The paper endeavors to gain an insight into their citation behavior to gender, age, qualification, and publications. An online questionnaire survey was conducted in July 2020 to collect data from researchers who have been studying or completed their research degrees from the Institute of Information Management, University of the Punjab, Lahore-Pakistan. Data showed that almost half of the researchers published articles in journals. They preferred to cite: the most recent sources, articles written by reputable authors, highly cited sources, and articles which contain high-quality references. Researchers were motivated to cite open access and impact factor journals. There was no significant relationship between gender and any of the variables of citation behavior. However, only qualification affected the citation motivation of novice researchers. The findings may guide the policymakers about fund allocation to research projects.